(untitled) (Journal of Agriculture and Natural Resources, 2021)
Capsicum is one of the high value vegetable crops in Nepal. Its demand in kitchen is increasing due to urbanization and increased awareness on its health benefit. Its commercial cultivation has been started in protected as well as open field conditions. It fetches higher price in market but has very short storage life under ordinary storage condition. An experiment was carried out to evaluate the modified atmosphere packaging (MAP) on extension of shelf-life of capsicum fruit. Fruit were harvested at full mature stage with smooth and shiny appearance from farmer’s field grown under protected condition at Chitwan, Nepal. The fruits were brought to postharvest laboratory of National Horticulture Research Centre, pre-cooled for 3-4 hours, cleaned with muslin cloth and packed in 25 micron Low Density Polyethylene (LDPE) packaging with different number of pinhole sized perforations viz. without pinholes, eight pinholes, sixteen pinholes, twenty four pinholes and control (without MAP). The study was conducted in completely randomized block design with five treatments and four replications. Fruits were kept at coolbot storage (9.8+2 ºC, 86+5% RH) till 30 days and analyzed for various postharvest physical, chemical and physiological parameters at every 10, 20 and 30 days of storage. The result showed that LDPE packaging influenced on reduction of physiological loss in weight (PLW), spoilage loss, ascorbic acid content, TA, freshness, firmness and shelf life. The modified atmosphere packaging (MAP) without pinholes showed the minimum PWL (1.71%) and the optimum fruit freshness (4.76) but the spoilage loss was the maximum (14%). Among the packaging, MAP with 8 pinholes maintained majority of postharvest quality retention with reduced physiological loss in weight (4.15 %), freshness (4.5) and spoilage loss (2%).